2019
DOI: 10.1155/2019/4029217
|View full text |Cite
|
Sign up to set email alerts
|

The Influence ofTLR4,CD14,OPG, andRANKLPolymorphisms in Periodontitis: A Case-Control Study

Abstract: The pathogenesis of periodontitis involves a complex interaction between the microbial challenge and the host immune response. The individual immunoinflammatory response has a great contribution in the pathogenesis of the disease and becomes a trigger in the process of bone remodeling which is a characteristic of the disease. Thus, the aim of this study was to evaluate the influence of the TLR4 A896G (rs4986790), TLR4 C1196T (rs4986791), CD14 C-260T (rs2569190), RANKL (TNFSF11, rs2277438), and OPG (TNFSF11B C1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 79 publications
2
8
0
1
Order By: Relevance
“…After multivariate analysis we observed a tendency (limited by the low statistical power) of men to be predisposed to the disease when in the presence of some polymorphisms in the inflammasome, cytokine and cytokine receptor genes, regardless of cigarette use. Previous studies had found a correlation between immune gene polymorphisms and men's susceptibility to PD [77,78], including Southern Brazilians patients [13,79]. Thus, our data corroborates in emphasizing the importance of genetic factors in men's susceptibility to developing PD.…”
Section: Discussionsupporting
confidence: 89%
“…After multivariate analysis we observed a tendency (limited by the low statistical power) of men to be predisposed to the disease when in the presence of some polymorphisms in the inflammasome, cytokine and cytokine receptor genes, regardless of cigarette use. Previous studies had found a correlation between immune gene polymorphisms and men's susceptibility to PD [77,78], including Southern Brazilians patients [13,79]. Thus, our data corroborates in emphasizing the importance of genetic factors in men's susceptibility to developing PD.…”
Section: Discussionsupporting
confidence: 89%
“…Similarly, while comparing alleles between the study groups, mutant T allele was more common in TB patients than in healthy controls, but the difference was not statistically significant. For CD14 (−159 C>T) SNP, C allele is a reference allele in the Asian population [24]. The results of the current study are in agreement with Ayaslioglu et al (2013) who also performed SNP genotyping through PCR-RFLP and could not detect significant difference in allelic as well as in genotype distribution between TB patients [19].…”
Section: (B) Isotype Control Run On Cd45-percp and Cd14-fitc Plot (Csupporting
confidence: 86%
“…Periodontitis is a chronic inflammatory disease of the periodontium, primarily induced by microbial challenge and affecting tooth-supporting structures [22,23[. Immune reaction is the major player in the pathogenesis of periodontitis.…”
Section: Discussionmentioning
confidence: 99%